Data visualization on occupational accidents in Malaysia / Mohd Asri Atan - Atan, Mohd Asri (2022)
Data visualization is the graphical display of abstract information for two purposes: sense-making it also called data analysis and communication. Important stories live in our data and data visualization is a powerful means to discover and understand these stories, and then to present them to others. The information is abstract in that it describes things that are not physical. Statistical information is abstract. Whether it concerns sales, incidences of disease, athletic performance, or anything else, even though it doesn't pertain to the physical world, we can still display it visually, but to do this we must find a way to give form to that which has none. This translation of the abstract into physical attributes of vision such as length, position, size, shape, and color, to name a few can only succeed if we understand a bit about visual perception and cognition. In other words, to visualize data effectively, we must follow design principles that are derived from an understanding of human perception. Accident Workplace issues include total of death, total of accidents, total permanent disability, and total non-permanent disability. The objective consisting of developing data visualizations based on Organization Safety and Health information, analyses the factors that contribute to workplace Accidents,and the frequency of employee and employer daily routine also evaluate the data visualization using user acceptance test. The dataset was extracted from Portal Organization safety and health Malaysia Portal, then load and transform into Power BI application for dashboard visualization. It can be explained even more clearly by displaying visuals. As a result, it can raise awareness of a good Standard Operating Procedure (SOP). Data analytics using data visualization is a suitable tool because it helps students to understand how to reduce the number of accidents at work habits through visualization of their working routine